Consentement Ã€ Payer Et RentabilitÃ© D’une Innovation En Agro-Alimentaire : Cas Du DÃ©corticage MÃ©canique Et De La Fortification En Fer Du Sorgho Dans Le Nord-BÃ©nin - Agossadou, Morest M. T.; SÃªgla, Sandrine S.; AdÃ©gbidi, Anselme A.; KayodÃ©, Polycarpe A. P. (European Scientific Journal, ESJ, 2018)
The purpose of this study is twofold. Firstly, it is a question of assessing the determinants of the willingness to pay (WTP) of farming households in Thian, a village located in northern Benin, exposed to the risk of anemia, to benefit from an agro-food innovation aimed at reduce these risks : dehulling and iron fortification of sorghum. Secondly, there was talk of evaluating the financial profitability of this innovation. To do this, socioeconomic and financial data were collected from 90 chef-kitchens prepared to adopt the innovation, the operator in charge of shelling and fortification services, the supplier of shelling equipment and the supplier of iron. The contingent valuation method was used to collect respondents’ WTP and the linear regression model to identify the determinants of these WTP and calculate their mean value. In addition, the cash flow method was used to assess the financial profitability of de-hulling and fortification services. The results reveal that the WTP (whose average is 24.4 FCFA) is negatively influenced by the fact that the respondent belongs to the pilot phase of the project and the average quantity of sorghum devoted to the consumption of dibou (sorghum paste). In a context where the monetary discount rate is 12%, mechanical shelling and iron fortification of sorghum as an economic activity is not profitable.